Pensions and external effects of ageing; effects on distribution - Agneta Kruse; Kristian Nyberg (Lund University, School of Economics and Management, Department of Economics, 2004)
Ageing gives rise to concern about the sustainability of pay-as-you-go pension systems. One reform option suggested is to make the system actuarial by a tight connection between contributions and benefits. The incentives for the individual will then coincide with the interest of the pension collective. However, the individual actions – fertility decisions, working hours, timing of retirement – also contain a collective part not taken into consideration in the individual's utility maximisation, a 1/N problem. As pay-as you-go systems are indexed by growth, the index (rate of return) is influenced by these actions even if the system is 'actuarially fair'. We trace the effects of changes in fertility and early exit/changes in working hours on different generations in an overlapping generation model. The economic model (a stylised model of the economy in aggregate and the pension system) is fitted into a simulation model. We show that the collective effect /external effects are far from negligible. Different measures to cope with these effects are discussed.
Keywords: D62; H55; J26; 330; pensions; demographics; external effects; OLG-model